Urgensi Pengaturan Kewarganegaraan Ganda Bagi Diaspora Indonesia - Charity, May Lim (Mahkamah Konstitusi Republik Indonesia, 2016)
The need for dual citizenship regulation seems increasingly prominent and becomes an issue that continues to be striven by the Indonesian Diasporas in various countries around the globe. Dual citizenship has become the dream of the Indonesian Diasporas in various countries since many Indonesian citizen Diasporas with a single citizenship often encounter various obstacles and limitations. The Indonesian citizenship law is today based on the principle of single citizenship. This principle has been even adhered since the proclamation of August 17 1945, under the enactment of Law Number 3 of 1946 on Citizenship of the Republic of Indonesia, which was later replaced by Law Number 62 of 1958 on Citizenship of the Republic of Indonesia and amended by Act Number 12 of 2006 on Citizenship of the Republic of Indonesia and the Government Regulation Number 2 of 2007 on Procedures for acquisition, loss, deprivation, and reacquisition of Citizenship of the Republic of Indonesia. Nowadays, the demands for the implementation of unlimited dual citizenship are under the considerations for the Government and the House of Representatives of the Republic of Indonesia to amend Act Number 12 of 2006. It is not only for the demands of the Indonesia diaspora to the implementation of unlimited dual citizenship, but it is also for the reality of the development of globalization today. The implementation of dual citizenship for Indonesian diaspora is a necessity. In addition, it is based on the reality of globalization and the spirit of the constitution that protects all the entire homeland of Indonesia, including Indonesian citizens residing abroad.